Legal Status of the Object of the Fiduciary Determined as State Confiscated Goods that Have Been Auctioned - Martin Batara Tambunan; Suherman Suherman; Heru Sugiyono (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this study is to analyze the legal status of fiduciary collateral objects designated as state-confiscated assets that have been auctioned, and to examine the resolution of the state's rights in confiscating and auctioning fiduciary collateral objects in relation to the rights of financing companies as fiduciary creditors whose claims remain unsettled. This study employs a normative juridical research method using statutory, case, and conceptual approaches. The results show that fiduciary collateral objects confiscated and auctioned by the state do not automatically nullify the creditor’s rights, as the principle of droit de suite entitles creditors to claim the object or the proceeds from its sale. Regulatory ambiguity creates legal uncertainty and discourages fiduciary-based financing practices. From a justice perspective, the state must not arbitrarily execute assets without considering the legitimate rights of creditors. Resolution of the conflict between the rights of the state and creditors must be carried out proportionally through criminal, civil, or non-litigation avenues, in order to establish a balance between law enforcement and creditor protection, thereby maintaining stability in the financing sector.